Autoimmune Hepatitis: Tolerogenic Immunological State During Pregnancy and Immune Escape in Post-partum - Bozward, Amber G.; Wootton, Grace E.; Podstawka, Oskar; Oo, Ye H. (Frontiers in Immunology, 2020)
The maternal immune system engages in a fine balancing act during pregnancy by simultaneously maintaining immune tolerance to the foetus and immune responses to protect against invading organisms. Pregnancy is an intricately orchestrated process where effector immune cells with foetal specificity are selectively silenced. This requires a sustained immune suppressive state not only by expansion of maternal Foxp3+ regulatory T cells (Tregs) but also by leaning the immune clock towards a Th2 dominant arm. The foetus, known as a semi-allograft or temporary-self, leads to remission of autoimmune hepatitis during pregnancy. However, this tolerogenic immune state reverts back to a Th1 dominant arm, resulting in post-partum flare of AIH. Various hormones play a significant role in endocrine-immune axis during pregnancy. The placenta functions as a barrier between the maternal immune system and the foetus also plays a pivotal role in creating a tolerogenic environment during pregnancy. We review the evidence of immune tolerance during pregnancy and immune escape at post-partum period, focusing on patients with autoimmune hepatitis.